Brain Tumor in an In Vitro Fertilization–Facilitated Pregnancy: Fourth Ventricle Anaplastic Ependymoma in the Second Trimester - Ryskeldiyev, Nurzhan; Olenbay, Gabit; Auezova, Raushan; Killeen, Tim; Aldiyarova, Nurgul; Akhmetzhanova, Zauresh; Cesnulis, Evaldas; Akshulakov, Serik (Journal of Neurological Surgery Reports, 2016)
We present a case of fourth ventricle anaplastic ependymoma in a pregnancy which was the first result of three rounds of in vitro fertilization (IVF) and embryo transfer. Whether hormonal treatment can directly or indirectly precipitate brain tumors to develop or become symptomatic is unclear.
Keywords: brain tumor; anaplastic ependymoma; pregnancy; in vitro fertilization